The Relationship Between Knowledge, Parenting Patterns, and Infectious Diseases with the Incidence of Wasting - Berlian Nita Sari; Dewi Woro Astuti; Asep Jalaludin (Jurnal Kesehatan Cendikia Jenius, 2025)
Wasting remains a major public health problem in Indonesia. In Bandar Lampung City, the prevalence of wasting reached 8.4% in 2023, and in the working area of Kotakarang Public Health Center, it has continued to increase from 8.2% (2022) to 10.9% (2024). This study aimed to determine the relationship between knowledge, parenting patterns, and infectious diseases with the incidence of wasting among children under five. This quantitative study used a cross-sectional design and was conducted from June 7–28, 2025, in the working area of Kotakarang Public Health Center. The population consisted of 1,281 children aged 19–60 months, with 112 samples selected using stratified sampling. Data on knowledge, parenting patterns, and infectious diseases were collected through questionnaires, while wasting was assessed using anthropometric measurements. Data analysis was performed using univariate and bivariate analyses with the Chi-Square test. The results showed significant relationships between knowledge (p = 0.001), parenting patterns (p = 0.002), and infectious diseases (p = 0.001) with wasting incidence. Children whose mothers had low knowledge, poor parenting, or a history of infectious disease were at higher risk of wasting. Infectious diseases showed the strongest association (OR = 25.5).In conclusion, improving maternal knowledge, enhancing parenting practices, and preventing infectious diseases are essential to reduce wasting. Recommended: the health center should strengthen education, screening, counseling, and home visits focusing on nutrition, sanitation, and hygiene.